Inicial immunovirologic assessment of patients with HIV/Aids at a specialized assistance service - Tibúrcio, Alberto Saraiva (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: the advent of highly active antiretroviral therapy (HAART) has provided a larger better prognosis regarding HIV/aids. However, there is a huge percentage of people who perform lately the diagnosis of HIV infection, evidenced by the low level of CD4 at the beginning of clinical follow-up. Objective: to underscore the importance of early diagnosis of HIV infection, providing a multiprofessional preventive primary and also secondary intervention. Methods: survey of all records of the Specialized Assistance Service of the Oswaldo Cruz Policlinic, Porto Velho, RO, held in the months September to December 2009. We included patients who had CD4 counts and viral load performed shortly after diagnosis, aged thirteen years or more at the time of serological diagnosis (anti-HIV), and even without the use of HAART at the time of the assessments immunological (CD4 count) and virological (viral load) initials. CD4 counts and viral loads of the initial patients were stratified as to assess the risk of developing disease. Results: among the 303 patients, 31,3% had CD4 counts below 200/mm3 and viral load greater than 30,000/mm3, with 85.5% risk of developing aids within three years. Conclusion: the need for early diagnosis of HIV infection is still great, since many patients seek care at an advanced stage. The benefits of HAART, when introduced at an appropriate time, are indisputable. Campaigns for voluntary testing should be disclosed with greater intensity, with wide dissemination of the potential benefits of testing.